Gogol’s key to the poetry of Alexandr Kushner (on the material of selected works) - Sadzińska, Ewa (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
The paper discusses the reception of Gogol’s Dead Souls by Alexandr Kushner. The focus is on the direct comments on Dead Souls and its author to be found in Kushner’s essays, as well as on numerous references to Gogol in the form of reminiscences and literary allusions in selected poems. A detailed analysis can reveal interesting parallels and similarities in the poetics of both authors: the perception of things in close association with humans, the feeling of a special communication between man and object, referring to eternal images and motifs.